Immune Tolerance in Hemophilia-Principal Results from the International Registry - Mariani, G; Ghirardini, A; Bellocco, R (Thrombosis and Haemostasis, 1994)
40 Hemophilia Centers from the USA, Canada, Europe and Japan referred to the International Registry 204 patients with haemophilia A, treated by Immune Tolerance (IT) Protocols over the past two decades because of the presence of an inhibitor to FVIII. 82% of the patients were high responders, while IT was started with low levels of inhibitor (<10 BU) in most (57.3%) of the cases. 69 patients (33.8%) were given the highest FVIII dosage (≥200 IU/kg/day), 71 (34.8%) intermediate dosages (50 - <200) and 64 (31.4%) the lowest dosages (<50). Of 158 patients persevering with treatment long enough to judge the outcome thereof, 107 (67.7%) achieved tolerance, 12 (7,6%) had a partial response, while 39 (24.7%) did not respond. Multivariate logistic regression analysis showed that two variables were independently associated with the highest probability of success: the use of high dose protocols (≥100 IU/kg/day) (p <.0001) and the presence of low levels of inhibitor (<10 BU) at enrollment (p = .004). The Kaplan-Meier inhibitor-free survival curve showed that tolerance is longlasting: only 1 out of 107 patients relapsed and the longest documented tolerant patient has been inhibitor-free for 16 years. 129 hemophiliacs were HIV Ab-negative at enrollment; of the 118 HIV-screened after the treatment, 18 (13.9%) were found to be HIV Ab-positive. IT can indeed modify the natural history of inhibitors to FVIII in hemophilia.